Identity on the line: The meaning of Aboriginal and Non-Aboriginal youth hanging out on the streets and train stations in the south-east corridor of Perth - Botsis, Sasha (2013)
Executive Summary We performed a critical analysis on data originally collected from young people, service providers, and parents, contained in Save the Children’s Photovoice and Participatory Action Research projects. We employed an interpretative phenomenological approach with thematic analysis examining participants’ ascribed meaning, personal experiences, and observations of youth ‘hanging out’ on the streets or trains in the South-East corridor of Perth. Criminology and Identity themes emerged, and we drew attention to the merits of a positive, holistic view of youth, growing up in today’s society; for the development of social programs, future interventions, and participatory action research. We identify several sub-themes within Identity: Forming a strong cultural identity, particularly for ATSI youth The relational aspect of street presence The concept of safety for youth Grandparent care in ATSI families The concept of ‘free space’ We formed the following recommendations: Avoid framing problems and solutions based in a criminology rhetoric; The need to move from the scoping, to the first phase of the PAR project; Consultation with youth towards establishment of culturally appropriate programs, which empower emergent identities; The formation of local youth working groups, with an opportunity to design and work on specific interventions; The formation of local parent working groups, to ensure involvement of family with young people, increasing attachment and building relational identity; Immediate, proximal interventions with the whole family: Family Support programs/local parent working groups and primary caregivers The implementation of cultural programs run by Elders; Ensuring that local working groups are involved at all stages of planning and implementation of ‘alternative’ spaces or programs for youth, School/Education based initiatives involving family; and As a general recommendation, we point to the advantages of early interventions